MANAGEMENT OF NUTRIENT DEFICIENCY ON INCEPTISOLS TO IMPROVE MAIZE GROWTH - NURSYAMSI, DEDI; BUDIARTO, A.; ANGGRIA, L. (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2002)
Maize is very prospective to be developed in upland Inceptisols if supported by proper soil management and suitable varieties. Research aimed to study nutrient limiting factors of Inceptisols for the development of maize (Zea mays L.). Research had been conducted at chemical laboratory and green house of Center for Soil and Agroclimate Research in Bogor by using soil samples taken from Sukabumi, West Java. The green house experiment utilized minus one test method with randomized block design, eleven treatments, and three replications. Maize crop of Pioner C3 variety was used as plant indicator. Parameters employed in this experiment were: (1) the dry weight of 4 week old-maize, (2) plant nutrients uptake of N, P, K, Ca, Mg, S, Zn, and Cu; and (3) soil properties analyses on soil pH H2O, Org-C, total-N, P-HCl, K-HCl, P-Bray 1, P-Olsen,exchangeable Ca, Mg, and K, CEC, exchangeable Al and H, as well as Cu and Zn-DTPA. The results showed that N, P, K, Ca, Mg, S, Cu, and Zn fertilizations increased soil N, P, K, Ca, Mg, S, Cu, and Zn contents as well as plant nutrient uptake. Fertilization of Ca (lime) decreased soil exchangeable Al and H as well as plant Al uptake. The application of rice straw increased soil organic C and CEC, and also plant nutrient uptake. N, P, and K nutrients, and organic matter were found out as the primary constraints to maize growth in Inceptisols of Sukabumi. To solve the limiting factors, the soils need to be treated with 270-300 kg urea, 240 kg SP-36, 100 kg KCl, and 3-5 tons organic matter per ha. It is recommended that urea and KCl to be applied gradually : before planting, 4 and 6 weeks after planting, respectively. SP-36 fertilizer is mixed with urea and KCl and drown into the soil before planting. Organic matter was formerly composted and mixed with the soils during land preparation.